Avaliação dos parâmetros reprodutivos de reprodutores de Tambaqui Colossoma macropomum (Cuvier 1818) - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The evaluation of the reproductive parameters that influence the performance of the reproduction are of great importance for the determination of the reproductive efficiency and the knowledge of the quality of the gametes. The objective of this work was to analyze the quality of the gametes of the tambaqui Colossoma macropomum matrices and to verify their effects on the reproductive parameters and their influence on the reproduction performance. The study was carried out at the Balbina Technology and Production Center - CTTPA, located in the village of Balbina in the municipality of Presidente Figueiredo / AM. Two batches of tambaqui matings were studied: Captivity lot – were evaluated 8 males and 6 females with a mean weight of 6.63 ± 1.061 kg and 9.00 ± 0.894 kg, respectively. Wild lot - were evaluated 8 males and 6 females with average weight 5.75 ± 1.282 kg and 8.33 ± 1.506 kg respectively. The collections occurred during the breeding period of the species between October 2016 and January 2017. Samples were collected from semen and oocytes from each matrix to analyze the characteristics of the gametes, such as semen volume (mL), sperm count (%), motility (%), Motile time (s), sperm concentration (cells / mL), morphology (% normal) and semen viability (%), and females oocyte diameter and spawning rate. The fertilization rate was calculated to evaluate the reproductive performance of the fish. As the physical and chemical variables of the water, such as temperature, dissolved O2 and pH of the incubators, were not statistically different during the whole collection period. There was no significant difference between the weight of the matrices and the variables of sperm quality among the lots, except for the sperm concentration and the total number of spermatozoa. The fertilization rate between the two lots was no different. For the reproductive performance of the females, no significant differences were found between the lots for the variables of females weight, spawn weight, fertilization rate and oocyte morphometry. For the variables of reproductive performance among females, no correlation was observed between these parameters, except the relation between spawning rate and fish weight. The fertilization rate was not correlated with the variables of sperm quality, reproductive performance of females and environmental variables except for the temperature that showed a significant correlation. Thus, we conclude that breeding lots have a difference in sperm concentration and total sperm count. Increasing the temperature of the incubation water decreases the tambaqui fertilization rate in CTTPAQ - Balbina.
Keywords: Reprodução de peixe; Piscicultura; Fertilização de peixe; Reprodução de tambaqui; Desempenho reprodutivo de peixe; CIÊNCIAS AGRÁRIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA